On solving the minimization problem and the fixed-point problem for a finite family of non-expansive mappings in CAT(0) spaces. (4th March 2018) - Cuntavepanit, Asawathep; Phuengrattana, Withun
Abstract : In this paper, we propose a new modified proximal point algorithm for a finite family of non-expansive mappings in the framework of CAT(0) spaces. We establish Δ-convergence and strong convergence theorems under some mild conditions. Our results extend some known results which appeared in the literature.